(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to identify the influencing factors (quality of service provided, pricing process, and bank location) on customer loyalty (cognitive loyalty, situational loyalty, behavioral loyalty) of private commercial banks on the Syrian coast. The researcher relied on the deductive approach in thinking, and relied on the descriptive approach to describe the research variables and analyze them based on the primary data that were collected. It was collected through a questionnaire designed by examining the researcher with previous studies and literature, and in order to test the hypotheses, the researcher dumped the raw data into a database that was analyzed using the SPSS program version // 20. The research community is represented by clients of private commercial banks in Lattakia Governorate, and the researcher distributed the questionnaire to (177) clients from the research community, from which (170) questionnaires were retrieved, among which (9) questionnaires were not valid for analysis, and thus the number of questionnaires valid for analysis became ( 161) Questionnaire. The study concluded that there is a weak correlation between the quality of service provided and cognitive loyalty, one of the dimensions of customer loyalty of private commercial banks in the Syrian coast, as the correlation coefficient was 0.256 between the two variables, and there is an acceptable correlation between the factors affecting loyalty and the loyalty of customers of private commercial banks in the Syrian coast, as the coefficient The correlation was 0.650 between the two variables..